2010
DOI: 10.3109/07420528.2010.516705
|View full text |Cite
|
Sign up to set email alerts
|

Evening Preference Is Related to the Incidence of Depressive States Independent of Sleep-Wake Conditions

Abstract: Although evening preference has recently been identified as a risk factor for depression, it has not been substantiated whether evening preference is a direct risk factor for depressive states, or if it is associated secondarily through other factors, such as delayed sleep timing and shortened sleep duration. The objective of this study is to investigate associations in Japanese adult subjects between evening preference and incidence of depressive states, adjusting for various sleep parameters related to depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
135
4
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(156 citation statements)
references
References 65 publications
15
135
4
2
Order By: Relevance
“…Our results offer the first evidence of more frequent prescriptions of antidepressant medication among evening types. These findings are in line with studies indicating that morning types appear to be protected from depression (Kitamura et al, 2010), at least if they are not sleep-deprived (Selvi et al, 2010). In a previous study, we found that evening types were also more prone to sleep problems than other chronotypes (Merikanto et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our results offer the first evidence of more frequent prescriptions of antidepressant medication among evening types. These findings are in line with studies indicating that morning types appear to be protected from depression (Kitamura et al, 2010), at least if they are not sleep-deprived (Selvi et al, 2010). In a previous study, we found that evening types were also more prone to sleep problems than other chronotypes (Merikanto et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
“…Several earlier studies with relatively small sample sizes have demonstrated that evening types have a greater likelihood for depressive symptoms or major depression compared with other chronotypes (Abe et al, 2011;Antunes et al, 2010;Drennan et al, 1991;Chelminski et al, 1999;GasparBaba et al, 2009;Hasler et al, 2010;Hidalgo et al, 2009;Kim et al, 2010;Kitamura et al, 2010;Levandovski et al, 2011;Meliska et al, 2011;Selvi et al, 2010). Gaspar-Baba and colleagues (2009) have reported that evening types had more severe depressive symptoms, and Selvi and colleagues (2011) found that evening types were also more prone to attempt violent suicides than other chronotypes.…”
Section: Introductionmentioning
confidence: 99%
“…A excepción de unos pocos trabajos (Putilov, 2008;Taylor, Clay, Bramoweth, Sethi y Roane, 2011), la mayoría de las investigaciones han hallado asociaciones entre la tipología circadiana y sintomatología depresiva (Abe et al, 2011;Antunes, da Jornada, Ramalho e Hidalgo, 2010;Hidalgo et al, 2009;Hsu, Gau, Shang, Chiu y Lee, 2012;Kitamura et al, 2010;Levandovski et al, 2011;Mecacci y Rocchetti, 1998;Natale et al, 2005;Ong, Huang, Kuo y Manber, 2007;Pabst, Negriff, Dorn, Susman y Huang, 2009;Randler, 2011;Takeuchi, Oishi y Harada, 2005; Tzischinski y Shochat, 2011), así como con depresión mayor (Gaspar-Barba et al, 2009;Meliska et al, 2011;Selvi et al, 2010.). En la Tabla 1 se presentan los principales resultados existentes en el tema.…”
Section: Trastorno Afectivo Estacional Y Depresión Mayorunclassified
“…Circadian misalignment and sleep disruptions in patients with mood disorders have been linked to abnormal daily patterns of gene expression, hormonal secretion, body temperature, and cognitive and behavioral functions (Wulff et al, 2010). An additional indication that circadian misalignment contributes to depressive symptoms is the finding that ET people are prone to depressive symptoms (Chelminski et al, 1999;Giannotti et al, 2002;Hidalgo et al, 2009, Kitamura et al, 2010). …”
Section: Mood Disordersmentioning
confidence: 99%